A Novel Plant Growth Regulator Alleviates High‐Temperature Stress in Maize. (1st November 2018) - Tao, Qun; Zhou, Yuyi; Guo, Qing; Liu, Yingru; Yu, Sha; Yu, Chunxin; Zhang, Mingcai; Li, Zhaohu; Duan, Liusheng
Abstract : Core Ideas: This study examined a new way to mitigate the effects of HTS on spring maize. B2 had similar effects to ABA on alleviating maize yield penalty caused by HTS. B2 reduced plant height and ear height. Adopting spring maize ( Zea mays L.) to replace part of a winter wheat ( Triticum aestivum L.)–summer maize rotation system can mitigate agricultural water scarcity in the North China Plain. The main obstacle to increasing spring maize production is high‐temperature stress (HTS) at grain‐filling stage. In this study, a novel plant growth regulator (2, 4‐dichloroformamide cyclopropane acid [B2]), based on the structures of abscisic acid (ABA), pyrabactin, and coronatine, was used to reduce maize yield penalty imposed by HTS. Field experiments were conducted to investigate the effects of B2 on alleviating maize yield penalty caused by HTS in 2015 and 2016. The hybrid maize cultivar Zhengdan958, which is widely planted across China, was grown at a density of 67, 500 plants ha −1 . Water, B2, and ABA were applied to maize foliar surfaces at the ninth‐expanded‐leaf stage. Application of B2 significantly increased grain yield by 8.5% by increasing thousand‐kernel weight and decreasing bare tip length compared with the control. Additionally, B2 significantly increased the SPAD value and ABA content of the ear leaf, enhancing net photosynthesis rate and heat resistance. Application of B2 also improved grain‐filling rate, grain volume, and grain dry weight, which contributed to higher grain yield. Moreover, B2 decreased plant and ear height, neither of which was affected by ABA. These results indicate that B2, with a biological activity similar that of ABA, could help maintain relatively higher photosynthetic capacity, heat resistance, and grain‐filling rate during the grain‐filling stage under HTS, providing a stable method to increase grain yield.